DINAMIKA PERTUMBUHAN POHON DI HUTAN RESTORASI BODOGOL TAMAN NASIONAL GUNUNG GEDE PANGRANGO, JAWA BARAT - Sadili, Asep; Salamah, Andi; Mirmanto, Edi; Kartawinata, Kuswata (Berita Biologi, 2023)
The Restored Forest (RF) in Bodogol, Gunung Gede Pangrango National Park (GGPNP) is located in the degraded lowland forest area. The Bodogol RF constituted the area of the ecosystem restoration program, where the initial tree planting was carried out by Mrs. Megawati Soekarnoputri the 5th President of the Republic of Indonesia. In that restored forest area, a study was conducted by establishing one hektare plots. We recorded 26 tree species and 16 families, including 14 tree species that were used in the restoration, four cultivated species, and eight species that naturally enter the site as new arrival (recruitment). The total basal area was 7.47 m2/Ha and tree density was 256 trees/Ha. The mean diameter growth was 1.78 cm/year, and the highest diameter growth was Hibiscus tilliaceus (2.42 cm/year). The mean total height growth was 0.52 m/year, and the highest was Paraserianthes falcataria (0.85 m/year). The density of Toona sureni was very high (61 trees/Ha) and in the future it ay dominate the forest will, therefore other tree species native to Mt. Gede-Pangrango should be planted to enrich the present restored forest so as to encourage the development of mixed lowland or montane forests similar to the original climax forests with high species diversity. Structurally, about 50 % of the RF has been achieved, but species composition still needs further enrichment either by active intervention of planting native TNGGP species if deemed necessary or by allowing succession to take place naturally, although it will take a very long time.